Respostas
respondido por:
1
2a/3 + b = 4 (mmc) x/2 - 3 = y
a + 5 = 3b x = y/2 + 3
2a + 3b = 12 x -6 = 2y
a - 3b = -5 2x = y + 6
3a = 7
x = (y+6) /2
a = 7/3
substituindo em
a + 5 = 3b
7/3 + 5 = 3b
3b = (7+ 15) /3
b = 22/9
a + 5 = 3b x = y/2 + 3
2a + 3b = 12 x -6 = 2y
a - 3b = -5 2x = y + 6
3a = 7
x = (y+6) /2
a = 7/3
substituindo em
a + 5 = 3b
7/3 + 5 = 3b
3b = (7+ 15) /3
b = 22/9
gelcale:
OK, MUITO OBRIGADA
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás